Percutaneous fully endoscopic surgical management of the ruptured epidural catheter: Rescue of the novice anesthesiologist from his dilemma - Kong, Weijun; Du, Qian; Xin, Zhijun; Cao, Guangru; Liu, Dexing; Wei, Yiyong; Liao, Wenbo (Frontiers in Surgery, 2022)
Background Epidural nerve block and analgesia are basic anesthetic techniques for anesthesia. Epidural catheter rupture and partial retention are adverse events and rare complications of epidural catheterization technique. The probability of occurrence when applied by novice doctors is high. Removal of the residual catheter by conventional surgery causes more trauma and bleeding, slows recovery, and may causes medical disputes. We hypothesized that percutaneous spinal endoscopy a safe and effective remediation technique. This study was to analyze the efficacy and safety of removing the residual dural catheter by a percutaneous full-endoscopic technique(PFET) and discuss the clinical technique and precautions. Methods This was a retrospective analysis of 7 patients with ruptured epidural catheters treated in our department from October 2015 to October 2019 using the PFET to remove the remaining epidural catheter. The operation time, intraoperative bleeding volume, surgical complications, and neurological symptoms before and after surgery were recorded. The Self-Rating Anxiety Scale (SAS) was used to assess the anxiety level of the anesthesiologist and the patient before and after the catheter removal operation, and the postoperative low back pain VAS score was recorded. Results The remaining epidural catheter was successfully removed from all 7 patients. The operation time was 54.14 ± 14.45 (32-78) minutes, and the intraoperative blood loss was 9.134 ± 3.078 (5-15) ml. There were no cases of dural damage, cerebrospinal fluid leakage, sensorimotor dysfunction of the lower limbs, or bowel dysfunction. The anxiety symptoms of the patient and the anesthesiologist disappeared after removal of the residual epidural catheter. The patients' postoperative back pain VAS score was 0 to 2 points. Conclusion PFET is a safe and effective minimally invasive technique for removing residual epidural catheters. It causes less trauma and less bleeding, allows a faster recovery. It does not affect the recovery of patients from other surgical operations and reduces both medical risks and medical costs. At the same time, it avoids or reduces the occurrence of medical disputes and eliminates the pressure on novice anesthesiologists regarding similar adverse events.